2019
DOI: 10.1097/cej.0000000000000476
|View full text |Cite
|
Sign up to set email alerts
|

The effect of NSAIDs exposure on breast cancer risk in female patients with autoimmune diseases

Abstract: Both breast cancer and autoimmune diseases (ADs) are predominant in women. NSAIDs are common medications for AD. Evidence on the association between NSAIDs use and breast cancer risk is controversial. We investigated the association between NSAIDs exposure and breast cancer risk in female patients with AD. AD patients older than 18 years of age were enrolled from Taiwan Longitudinal Health Insurance Database 2005. The NSAID users were defined as AD patients who had ever taken NSAIDs for at least 3 months betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Our results are consistent with the majority of results from prospective studies, suggesting no reduced risk of breast cancer with NSAID use whether the exposure considered was any type of NSAIDs [ 12 , 27 29 ], high-dose aspirin [ 17 , 27 , 30 ], ibuprofen [ 27 , 31 , 32 ], COX-2 inhibitors [ 27 , 30 ], or non-aspirin NSAIDs [ 17 , 33 38 ]. However, some other studies have reported a reduced risk of breast cancer with NSAIDs (any type) [ 16 , 32 , 35 , 39 ], high-dose aspirin [ 32 ], ibuprofen [ 16 ], COX-2 inhibitors [ 11 , 14 , 16 , 39 ], or non-aspirin NSAIDs [ 29 , 30 , 40 , 41 ] while a few other studies indicated an increased risk of breast cancer with NSAIDs (any type) [ 10 , 31 ], high-dose aspirin [ 10 ], ibuprofen [ 10 ], or COX-2 inhibitors [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with the majority of results from prospective studies, suggesting no reduced risk of breast cancer with NSAID use whether the exposure considered was any type of NSAIDs [ 12 , 27 29 ], high-dose aspirin [ 17 , 27 , 30 ], ibuprofen [ 27 , 31 , 32 ], COX-2 inhibitors [ 27 , 30 ], or non-aspirin NSAIDs [ 17 , 33 38 ]. However, some other studies have reported a reduced risk of breast cancer with NSAIDs (any type) [ 16 , 32 , 35 , 39 ], high-dose aspirin [ 32 ], ibuprofen [ 16 ], COX-2 inhibitors [ 11 , 14 , 16 , 39 ], or non-aspirin NSAIDs [ 29 , 30 , 40 , 41 ] while a few other studies indicated an increased risk of breast cancer with NSAIDs (any type) [ 10 , 31 ], high-dose aspirin [ 10 ], ibuprofen [ 10 ], or COX-2 inhibitors [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among a dozen prospective studies with data on duration or dose of use, a few observed a dose/duration response [ 16 , 28 , 32 , 40 ]. In our study, the NSAID-breast cancer association did not differ according to duration or dose of use.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the decrease in the incidence of BC in the early 21st century was, at least in part, related to the decline in the use of postmenopausal hormone therapy after the launch of the Women's Health Initiative trial (Ettinger, Quesenberry, Schroeder, & Friedman, ). In addition, older women seem to be more likely to take nonsteroidal anti‐inflammatory drugs (NSAIDs) as they age because of the onset of various diseases, and NSAID exposure has been shown to be associated with a decreased risk of BC (Hung et al, ). A worse prognosis may be related to the type of surgery performed.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, although nonsteroidal anti-inflammatory drugs (NSAIDs) have been traditionally known for their analgesic, anti-inflammatory and antipyretic effects [2], in recent years several epidemiological, preclinical, and clinical studies support their chemopreventive and chemotherapeutic potential use for cancer treatment [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Remarkably, numerous systematic reviews and meta-analyses to date suggest that NSAIDs could be associated with a reduced risk of breast cancer, particularly aspirin (ASA) [18][19][20][21][22][23][24][25]. Recently, ASA was shown to have a potential preventive effect especially in hormone receptor positive tumors or in situ breast tumors in postmenopausal women [8,21].…”
Section: Introductionmentioning
confidence: 99%